The Effectiveness of Papaya on Increasing Breast Milk Production in Nursing Mothers at Bd. Yuliati Clinic in 2023 - Feny Handayani; Omega DR Tahun (Global Health Science Group, 2023)
The global strategy of infant and child feeding states that prevention of infant mortality is exclusive breastfeeding for 6 months along with continued breastfeeding until the age of 2 years or more. But there are still many breastfeeding mothers who experience a decrease in milk production. Research has reported that papaya fruit that grows a lot in Indonesia has the potential to increase breast milk through lactagogum content. This study aims to analyze the effect of papaya fruit on increasing breast milk production. This study was conducted in the period April – May 2023 on 35 postpartum mothers day 2 . Papaya fruit is given for 7 days as much as 600 grams gr, 3 times a day and observed on the 9th postpartum day. Statistical analysis using independent t-test Bivariate analysis showed that there was an effect of giving papaya fruit as much as 600 grams for 7 days on increasing maternal breast milk and statistically the difference was considered significant, because the p-value of 0.039 < 0.05.